A field experiment to determine the effect of dry-season irrigation on vegetative and reproductive traits in the wet-deciduous tree Bonellia nervosa. (January 2020) - Sánchez, Octavio; Quesada, Mauricio; Dirzo, Rodolfo; Schlichting, Carl D.
Abstract: Seasonally dry tropical forests (SDTFs) stand out by the diversity of phenological patterns used by plants to deal with dry periods. Although the predominant phenological pattern is dry deciduousness, in Mesoamerican SDTFs the heliophilous tree species Bonellia (formerly Jacquinia ) nervosa displays an unusual inverted leaf phenology, producing and holding leaves through the dry season while becoming deciduous in the rainy season. Applying a dry season irrigation field experiment (no water, low watering, high watering), we studied the consequences of contrasting water availability from a phenological plasticity response perspective. Contrary to our expectations, our results show no effect of irrigation treatment on leaf phenology. In addition, mid-day twig water potential showed no significant differences across treatments, but reproductive phenological responses varied among treatments: canopy flowering per cent decreased gradually until the beginning of the wet season in all treatments; meanwhile canopy fruit per cent showed a significant decline under low irrigation. Finally, non-structural carbohydrate concentration (starch) was significantly higher in the high irrigation treatment. Our results showed that inverted leaf phenology remains unaffected regardless of supplemental water availability, and suggest a reallocation of non-structural carbohydrates to fruits and seeds in high-irrigation treatments. Given the current and expected increase in extreme drought events, investigations on the responses of trees of different phenologies, including those of inverted leafing such as Bonellia nervosa, are warranted.